Perlakuan akuntansi belanja barang dan jasa pada Pengadilan Negeri Tondano - Rembet, Injilly Sefanya Karyn; Saerang, David P. E.; Wokas, Heince R. N. (Yayasan Widyantara Nawasena Raharja, 2025)
The accounting treatment refers to the rules and steps taken in the accounting process, including the recognition, measurement, and disclosure of financial information in financial statements, whether for companies or government entities. The success of budgeting is typically assessed through the preparation of a Budget Realization Report (LRA). This report provides an overview of the sources, allocation, and utilization of economic resources managed by the central or regional government, illustrating the comparison between the budget and its actual realization within a specific reporting period. This study aims to analyze whether the accounting treatment in the Tondano District Court’s Budget Realization Report aligns with the Government Accounting Standards (SAP) as stipulated in Government Regulation No. 71 of 2010. Using a descriptive qualitative method, the study finds that the accounting treatment of goods and services expenditures in the Tondano District Court complies with PSAP 02 and Government Regulation No. 71 of 2010 on Government Accounting Standards.